2020
DOI: 10.5539/jfr.v9n5p78
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds, Antioxidant Activities, and Health Beneficial Effects of Selected Commercial Berry Fruits: A Review

Abstract: Epidemiological studies have provided the evidence that regular consumption of fruits and vegetables reduce the risk of pathological condition such as cardiovascular disease, cancer, inflammation, and aging. Among fruits, berries are considered as superfruits due to their highly packed phytochemicals comprising phenolic acids, flavonoids viz. flavonols, flavanols, and anthocyanins. These bioactive compounds are associated with significant antioxidant, antidiabetic, antiinflammation, and anticancer properties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 132 publications
(139 reference statements)
0
9
0
Order By: Relevance
“…The product ions were at m / z 353, m / z 335, m / z 191, m / z 179 due to the loss of [M-H-C 9 H 6 O 3 ], [M-H-C 9 H 8 O 4 ], [M-H-C 18 H 12 O 6 ] and [M-H-C 16 H 16 O 8 ] from the precursor molecule, respectively [ 60 ] and had been identified in strawberries, raspberries, blueberries. 3-Feruloylquinic acid (Compound 10, precursor ([M − H] − m / z at 367.1038) was present in strawberries and raspberries, confirmed by the fragments at m / z 298, m / z 288, m / z 192 and m / z 191, corresponding to the loss of [M-H-3H 2 O 2 -CH 3 ], [M-H-H 2 O-CH 3 -HCOOH], [M-H-C 7 H 11 O 5 ] and [M-H-C 10 H 8 O 3 ], respectively [ 61 ] and previously observed in cherries [ 57 ]. 3-caffeoylquinic acid (Compound 12) with precursor [M –H] − m / z at 353.0884 present in strawberries and raspberries, yielded product ions at m / z 253, m / z 190 and m / z 144 due to the corresponding loss of HCOOH-3H 2 O, C 6 H 5 O 2 -3H 2 O and C 7 H 11 O 6 -H 2 O, respectively, from the precursor molecule [ 61 ].…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The product ions were at m / z 353, m / z 335, m / z 191, m / z 179 due to the loss of [M-H-C 9 H 6 O 3 ], [M-H-C 9 H 8 O 4 ], [M-H-C 18 H 12 O 6 ] and [M-H-C 16 H 16 O 8 ] from the precursor molecule, respectively [ 60 ] and had been identified in strawberries, raspberries, blueberries. 3-Feruloylquinic acid (Compound 10, precursor ([M − H] − m / z at 367.1038) was present in strawberries and raspberries, confirmed by the fragments at m / z 298, m / z 288, m / z 192 and m / z 191, corresponding to the loss of [M-H-3H 2 O 2 -CH 3 ], [M-H-H 2 O-CH 3 -HCOOH], [M-H-C 7 H 11 O 5 ] and [M-H-C 10 H 8 O 3 ], respectively [ 61 ] and previously observed in cherries [ 57 ]. 3-caffeoylquinic acid (Compound 12) with precursor [M –H] − m / z at 353.0884 present in strawberries and raspberries, yielded product ions at m / z 253, m / z 190 and m / z 144 due to the corresponding loss of HCOOH-3H 2 O, C 6 H 5 O 2 -3H 2 O and C 7 H 11 O 6 -H 2 O, respectively, from the precursor molecule [ 61 ].…”
Section: Resultsmentioning
confidence: 80%
“…Gallic acid 4- O -glucoside was identified in strawberries and blackberries, whereas the compounds gallic acid and 2,3-dihydroxybenzoic acid were only present in strawberries, however, the compound 2-hydroxybenzoic acid was present in strawberries, raspberries and blueberries. In previous studies, gallic acid 4- O -glucoside presence was observed in blueberries and bilberries [ 57 ], compound gallic acid found in various maturity stages in strawberries [ 58 ] and 2,3-dihydroxybenzoic acid was observed in hops and juniper berries [ 21 ]. Compound 4 identified as protocatechuic acid 4- O -glucoside ( m / z 315.0707) was present in both modes and the product ions at m / z 153 indicating the loss of hexosyl moiety (162 Da) from precursor molecule [ 54 ] and was only detected in strawberries.…”
Section: Resultsmentioning
confidence: 99%
“…This situation brings with it the necessity of expanding the cultivation of productive species with high nutritional value. For this reason, studies on the nutritional and commercial values of functional fruits especially berries such as chokeberry, bilberry, blackcurrant, blueberry, cranberry and European cranberrybush (ECB), which are widely found in nature as a wild have increased considerably recently [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate (CHO)'s and minerals play an important role in critical functions such as energy metabolism, neural transmission, muscular activity, bone formation, antioxidant activity; vascular constriction, maintaining normal acid-base balance, osmotic pressure, and normal water balance in human body, normal water balance, and osmotic pressure (Talwar and Srivastava, 2002;Srilakshmi, 2006). Recently, the attention on phenolics significantly increased due to their importance on human health as bioactive compounds having antimutagenic, chemopreventive, anticarcinogenic antioxidant and antimicrobial activities (Nemzer et al, 2020;Mohammed et al, 2019;Mohammed et al, 2020). Apart from the medicinal and pharmaceutical potentials phenolics have also great potential to be used in food, agriculture, and cosmetic industries.…”
Section: Introductionmentioning
confidence: 99%